Believing: our thirty-year journey to end gender violence - Hill, Anita (Viking, 2021)
Introduction: boiling the ocean -- Our state of denial -- Frozen -- A "recurrent feature of our social experience" -- The myth of the woke generation -- Institutional neglect -- The millennial workplace -- A woman's worth: representation, violence, and equality -- Victim shaming -- Politics: rage, compromises, and backlash -- Accountability.